Optimizing propulsion in swimming by rotation of the hands - Ungerechts, B. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
The coach who is attempting to assist less talented swimmers is forced to increase his knowledge of the biomechanics of swimming because the average swimmer needs explicit instructions to approximate the proficiency of a champion. Biomechanics may be able to determine if the functional properties of the locomotor apparatus might fit the mechanical or the hydrodynamic demands. The hydrodynamic principles of competitive swimming have been recognized and listed (Reischle, 1976). The application of these principles in coaching or teaching, however, is in its early stages. Normally, it is hoped that swimmers acquire a feeling for the details of highly skilled swimming through trfal~and error. In the early stages of learning, while obtaining the idea of the gross pattern this may be reasonable and sufficient. However, in the advanced stages this sort of learning will take a long time, perhaps too long for the swimmer to remain competitive. Knowledge of the functional properties of the locomotor system may help the swimmer to improve his performance